Tekstin nautinnosta Kuvan luennasta kirjoittamisen aktiin - Kihlman, Asta (Tietolipas, 2022)
The book explores the discourses of modernism, contemporary art and art history writing as well as their interdisciplinary values and boundaries - and cases that do not fit within these boundaries.The articles explore the meanings of junk and relics, high art, design, and the intimate experience of art and public criticism. The themes explored in the book expand our views on the queer potential of colour, the meaning of detail, and the relationships between visual art and writing. The fourteen peer-reviewed case studies in the volume offer new insights from the fields of visual cultural studies, art history and gender studies. The articles in the anthology do not rely strictly on disciplinary boundaries but also open themselves up to broader fields of culture.